Sources and export of nutrients associated with integrated multi-trophic aquaculture in Sanggou Bay, China - R Li (Inter-Research, 2016)
Field observations were made from 2012 to 2014 at an integrated multi-trophic aquaculture (IMTA) site in Sanggou Bay (SGB), China, to characterize the nutrients associated with aquaculture activities, and to assess the effects of aquaculture on nutrient cycles in the bay. Dissolved inorganic and organic nutrient levels were measured in rivers, groundwater, and SGB. Seasonal variations in nutrient concentrations were detected in the rivers, particularly enrichment of dissolved inorganic nitrogen (DIN) and silicate (DSi). Nutrient concentrations showed considerable seasonal variation, with higher and significantly different concentrations occurring in autumn than in the other seasons. The composition and distribution of nutrients were also affected by the species being cultured. Dissolved organic nitrogen and phosphorus (DON and DOP) accounted for 27 to 87% of total dissolved nitrogen and 34 to 81% of total dissolved phosphorus, respectively. Phosphorus may be a potentially limiting nutrient for phytoplankton growth in summer. Nutrient budgets were developed based on a simple steady-state box model. These showed that bivalve aquaculture was the major source of PO43- (contributing 64% of total influx) and led to increased riverine fluxes of PO43-. The results indicated that substantial quantities of nitrogen and DSi accumulated in sediments or were transformed into other forms (e.g. phytoplankton cell composition or particles). Large quantities of DIN and PO43- were removed from the bay through harvesting of seaweeds and bivalves, which represented up to 64 and 81% of total outflux, respectively. The results show that aquaculture activities play the most important role in nutrient cycling in SGB.